Kinerja BUMD dalam Menunjang PAD dan Masuknya Investasi/Investor ke Kabupaten Bandung (Suatu Subtema dari Manajemen Pembangunan Daerah) - Hayuni Rachmawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Manager take up by nepotism, managing unprofesionalized, high operational cost and maintenance but low product sales price (on PDAM) caused unpropfitable per /annum. The old machine and equipment need bigger investment. Loans are borrowing but unpayable. Thatâ€™s all of the problem wcich leat unfitnesess BUMD in Indonesia. Also, BUMD for PDAM and BPR in Bandung regency. Pushing forward the fact and bring around the data about:Taking hold of manager handed by birocrate saying with nepotismLow contribution of BUMD profit to PAD for example : PDANM and BPR with only one nol comma to compare with kind another PAD. Each about average 1.65% the real ( 2003) and average 0.66% on budgeted (2004).The PDAM tarifâ€™s tendencied lower than operational cost and maintenance although there are merchant/service tarifâ€™s and industrial corporation tarifâ€™s with fixed buy Pemda. Higher than cost.Â Maybe at means for cross subsidied to another tarifâ€™s. But always following losses each /year.BUMD (PDAM) performance said that corporation are in solvabel but not liquid. And earnig power are low, while in the budgeting are not really. Maybe it means not to high made planed.BUMD ( BPR) performance said that corporation are and solvabel and liquid, but earning power are low. This budget not considering cost efficiencies.Machine and equipment had been 35% used caused high cost for maintenance.Loan from year 1991 up to 2004 only paid 21% for foreign loan and 14% for domemestic loan.Limited due are : 2006 (before rescheduling), 2010 (after rescheduling) ut to 2017 (no rescheduling).Thatâ€™s all of phenomenon described for unfitnessess BUMD.If the BUMD must be bankrupt and close in, there for that only and economic action. But if not pissible like that, there have and alternatif is namely corporatisation. But must fit well.In corporatisation be able to do think % portion for Pemda and % portion and society. So that Pemda still have PAD and there are another aim PAD for example â€œTax Incomeâ€. Another point of view are bargaining some possible project invested to investor beginning from 2002 to 2004, agrobisnis project looks realized. None the other project. This act to do as sistitute to 79 private corporation which bankrupt in Bandung regency (BPS).